COPD : Heterogeneity and Personalized Treatment - Lee, Sang-Do (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This book explains how analysis of the heterogeneity of chronic obstructive pulmonary disease (COPD) enhances understanding of the condition and leads to improved, personalized treatment. State of the art knowledge is presented on a range of issues related to the heterogeneity of COPD, such as phenotypes (clinical, physiologic, radiologic, etc.), genotypes, and the tools to be used for dissecting heterogeneity (CT, MRI, biomarkers, etc.). Especially modern radiologic imaging holds promise in this context, and its role is described in detail with the aid of numerous illustrations. The implications of the heterogeneity for personalized treatment are clearly identified, with description of an appropriate tailored treatment strategy for each subgroup of patients. Information is provided on both current and emerging strategies, including bronchoscopic lung volume reduction and approaches to the management of pulmonary hypertension and comorbidities. This book will be a great asset in clinical practice and research for all who have an interest in COPD, a leading cause of morbidity and mortality worldwide.